Pemetaan Tematik, Teoretis, dan Metodologis Riset Kepatuhan Pajak ASN di Indonesia: Studi Systematic Literature Review 2020-2024 - Fahimatus Sania; Erlyna Tri Rohmiatun (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Tax compliance is a crucial element in supporting state revenue and reflects the integrity of the public bureaucracy. However, the level of tax compliance among State Civil Apparatus (ASN) in Indonesia still faces various challenges. To date, the literature on ASN tax compliance tends to be partial and does not provide a comprehensive overview of the evolution of theories and emerging methodological trends. This study aims to map the development of research related to ASN tax compliance in Indonesia during the 2020–2024 period through a Systematic Literature Review (SLR) approach. This study analyzed ten scientific articles obtained from national academic databases, focusing on the variables, theories, and methods used in previous research. The analysis was conducted qualitatively and descriptively to identify patterns of findings and research gaps. The study results indicate that ASN tax compliance is influenced by factors such as tax knowledge, sanctions, awareness, trust, institutional factors, and digital technology. This study contributes by developing a research map that integrates the Theory of Planned Behavior and Institutional Trust Theory as a basis for fiscal policy for ASN. These results provide a basis for the government to design more effective tax policies and training.